Patents, citations, and innovations : a window on the knowledge economy - Jaffe, Adam B. (MIT Press, 2002)
Innovation and technological change, long recognized as the main drivers of long-term economic growth, are elusive notions that are difficult to conceptualize and even harder to measure in a consistent, systematic way. This book demonstrates the usefulness of patents and citations data as a window on the process of technological change and as a powerful tool for research on the economics of innovation. Patent records contain a wealth of information, including the inventors' identity, location, and employer, as well as the technological field of the invention. Patents also contain citation references to previous patents, which allow one to trace links across inventions.The book lays out the conceptual foundations for such research and provides a range of interesting applications, such as examining the geographic pattern of knowledge spillovers and evaluating the impact of university and government patenting. It also describes statistical tools designed to handle methodological problems raised by the patent and citation processes. The book is accompanied by a set of auxiliary materials, including complete data on 3 million patents with more than 16 million citations and a range of author-devised measures of the importance, generality, and originality of patented innovations. This is available for download at http://mitpress.mit.edu/jaffecdcontents.